"The right place and the right time": A qualitative study of the decision‐making process of self‐initiated HIV testing among young adults. Issue 2 (12th February 2020) - Adebayo, Oluwamuyiwa W.; Williams, Jessica R.; Garcia, Ana
Abstract: Young adults continue to have very low rates of human immunodeficiency virus (HIV) testing, which contribute to transmission, late diagnoses, and poor health outcomes. The access and uptake of HIV testing among young adults can be improved by promoting self‐initiated testing (i.e., testing without the immediate recommendation of a clinician). Little is known, however, about how young adults self‐initiate HIV testing. The purpose of this study was to explore the decision‐making process of young adults who self‐initiated HIV testing. A qualitative descriptive study was conducted with 30 young adults aged 18–24 years. The findings from this study describe how young adults acknowledge their vulnerability to HIV infection and navigate the process of deciding to self‐initiate testing. Some subcategories include Self‐Convincing, Conversation Prompts, and The Right Place and Right Time . Findings from this study are pivotal for subsequent studies to further understand self‐initiated HIV testing among young adults and design targeted interventions that will improve testing uptake.